EXPLORING THE BIBLICAL AND CHRISTIAN TRADITION IN ALTERNATIVE DISPUTE RESOLUTION: A STUDY OF TRADITIONAL ADR MODELS AMONG THE ST. THOMAS CHRISTIANS IN KERALA, INDIA (Lex localis - Journal of Local Self-Government, 2025)
This study explores the traditional Alternative Dispute Resolution (ADR) practices among the St. Thomas Christians of Kerala, India, tracing their roots in Biblical teachings and Christian theological principles. Emphasizing reconciliation, forgiveness, and communal harmony, these faith-based mechanisms have historically provided culturally sensitive and restorative means of resolving conflicts within the community, complementing formal legal systems. Drawing on qualitative research, including interviews with clergy, elders, and scholars, alongside historical and theological analysis, the paper investigates how ADR among the St. Thomas Christians integrates Biblical mandates such as those found in Matthew 18:15–17 and 1 Corinthians 6, promoting dispute resolution internally through dialogue and moral accountability. The study highlights the role of parish councils and church elders as mediators, reflecting a blend of religious authority and indigenous customs adapted over centuries. Furthermore, it analyzes the impact of historical events, such as the Synod of Diamper, on these practices and their evolution amidst colonial and modern legal influences. By situating the St. Thomas Christian model within India’s pluralistic legal landscape, the research argues for the relevance and potential integration of such faith-informed ADR approaches into contemporary dispute resolution frameworks, emphasizing their restorative focus and community participation. The findings contribute to broader conversations on legal pluralism, restorative justice, and culturally embedded conflict management, offering valuable insights for enhancing ADR in diverse societies.